Mapping the operations and supply chain management field: a journal governance perspective. Issue 7 (3rd July 2017) - Burgess, Thomas F.; Grimshaw, Paul; Huaccho Huatuco, Luisa; Shaw, Nicola E.
Abstract : Purpose: The purpose of this paper is to address the following research question: how do the interlocking editorial advisory boards (EABs) of operations and supply chain management (OSCM) journals map out the field's diverse academic communities and how demographically diverse is the field and its communities? Design/methodology/approach: The study applies social network analysis (SNA) to web-based EAB data for 38 journals listed under operations management (OM) in the 2010 ABS Academic Journal Quality Guide. Findings: The members of EABs of the 38 journals are divided into seven distinct communities which are mapped to the field's knowledge structures and further aggregated into a core and periphery of the network. A burgeoning community of supply chain management academics forms the core along with those with more traditional interests. Male academics affiliated to the US institutions and to business schools predominate in the sample. Research limitations/implications: A new strand of research is opened up connecting journal governance networks to knowledge structures in the OSCM field. OM is studied separately from its reference and associated disciplines. The use of the ABS list might attract comments that the study has an implicit European perspective – however the authors do not believe this to be the case. Practical implications: The study addresses the implications of the lack of diversity for the practice of OM as an academic discipline. Social implications: The confirmation of the dominance of particular characteristics such as male and US-based academics has implications for social diversity of the field. Originality/value: As the first study of its kind, i.e. SNA of EAB members of OSCM journals, this study marks out a new perspective and acts as a benchmark for the future.